The Effect of the BRI People's Business Credit Program (KUR) on Entrepreneurship Development and People's Economic Growth in West Java - Sri Juminawati; Roosganda Elizabeth (Westscience Press, 2023)
Microcredit programs have emerged as powerful tools for poverty alleviation and economic growth in developing economies. This study investigates the impact of the BRI People's Business Credit Program (KUR) on entrepreneurship development and economic growth in West Java, Indonesia. Employing a mixed-methods approach, including quantitative survey data and qualitative insights from interviews and focus group discussions, the research reveals compelling findings. The quantitative analysis demonstrates a high level of participation in the BRI KUR program, with significant positive effects on entrepreneurship development indicators, such as business growth, employment generation, and income increase. Furthermore, areas with higher program participation exhibit noteworthy increases in GDP per capita and reductions in poverty rates. These results underscore the program's pivotal role in stimulating entrepreneurship and fostering economic growth at the regional level. Qualitative insights from program participants and stakeholders provide valuable context, emphasizing the program's accessibility, its impact on entrepreneurship culture, and the importance of addressing challenges for sustainable success. This research contributes to our understanding of microcredit program effectiveness, especially within the unique regional context of West Java. It offers insights for policymakers, financial institutions, and development agencies seeking to harness the potential of microcredit programs as drivers of economic transformation.